Defining the elements of a self and peer assessment system for academic institutions of public health in Africa as a precursor to accreditation: A study protocol - Neo R. T. Ledibane; Sean M. Patrick; Kuku V. Voyi (PLoS ONE, 2025)
Background Current challenges facing the overburdened health systems in Africa, warrant a review of the public health training and development of the health workforce for the attainment of the envisioned global goal of universal health coverage (UHC) and the United Nations Sustainable Development Goals (SDG). The integral components informing the relevance of public health education in the context of UHC comprise the academic workforce, curricula and the capacity of the academic institutions of public health. This study aims to assess the quality improvement strategies of academic institutions of public health with respect to the curriculum and the academic faculty staff within the WHO African region, in order to develop an institutional self- and peer-assessment tool to ensure the quality of public health education. Methods This study will be a three-phase, multicentre sequential mixed-methods design within the WHO African region, targeting 52 ASPHA (Association of Schools of Public Health in Africa)-affiliated institutions. Phase 1 will comprise a cross-sectional survey to determine the current programme assessment standards. Phase 2 will employ a modified Delphi method to reach consensus on these standards that will comprise a newly developed assessment tool. Phase 3 will pilot the tool through institutional self-assessment. MPH coordinators and department heads will participate. Convenience sampling and electronic questionnaires will be used. Quantitative data will be analysed using STATA 18, and ATLAS.ti for qualitative data. Projected outputs and impact The study findings are envisaged to result in a set of agreed standards reflecting the institutional arrangements to ensure quality postgraduate public health education in Africa. These standards, in the absence of regulation or formal accreditation, will be the basis of a self- and peer-assessment tool to enable the African academic institutions of public health to advance capacity development and monitor progressive educational goals suitable for local health needs, within the global context of the SDG and UHC implementation. Thus, laying the ground for a uniquely African accreditation system. The findings will be shared with the relevant stakeholders; ASPHA, the academic institutions of public health, and the scientific community at conferences and published in accredited journals.